Parasitological and Immunological study of the Effect of Chitosan and Chitosan Nanoparticles Loaded with Spiramycin on Toxoplasmosis - Hanaa Kamil Hamad (Journal of Global Pharma Technology, 2018)
This study was carried out to evaluate parasitological and   immunological of the effect of chitosan and chitosannanoparticles loaded with spiramycin on toxoplasmosis infected mice. After injection intra peritoneal with 103viable tachyzoites for acute infection, treatments given for seven days. Peritoneal fluid examination revealed a significant decrease in the number of Toxoplasmagondiitachyzoites in all treated infected mice compared with infected non-treated. The combined therapy gave better results than single. The best effect was observed in group of mice treated with spiramycin combined with chitosan nanoparticles. Also immunoglobulin Ig Manti body and gamma Interferon (INFγ), Tumor Necrosis Factor alpha (TNF-α) cytokines responses against T. gondii antigens were assessed by enzyme linked immunosorbent assays (ELISA) kits after treatment. In this study the findings indicated improvement of immune status after treatment.Keywords: Toxoplasma gondii, Nanochitosan, Spiramycin, Cytokines, ELISA.